2010
DOI: 10.1111/j.1349-7006.2010.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Long interspersed nuclear element‐1 hypomethylation is a potential biomarker for the prediction of response to oral fluoropyrimidines in microsatellite stable and CpG island methylator phenotype‐negative colorectal cancer

Abstract: We investigated the clinical value of methylation of long interspersed nuclear element-1 (LINE-1) for the prognosis of colorectal cancer (CRC) and for the survival benefit from adjuvant chemotherapy with oral fluoropyrimidines. LINE-1 methylation in tumor DNA was measured by quantitative methylation-specific PCR in 155 samples of stage II and stage III CRC. The presence of microsatellite instability and CpG island methylator phenotype (CIMP) were assessed and 131 microsatellite stable ⁄ CIMP) cases were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 38 publications
(53 reference statements)
1
53
5
Order By: Relevance
“…As mentioned above, both HCT116 and SW48 cell lines represent CIMP phenotype. 28) According to the report by Mossman et al, 29) HCT116 and SW48 cell lines are known to harbor epigenetic changes, and were among the most affected by DAC, which may suggest that regulation of DNA methylation in these cell lines is different from that in others. In addition, HCT116 and SW48 cells have been used for the analysis of DNA methylation.…”
Section: Fig 2 Msp Analysis Of the Upstream Region Of Tss In Colon mentioning
confidence: 99%
“…As mentioned above, both HCT116 and SW48 cell lines represent CIMP phenotype. 28) According to the report by Mossman et al, 29) HCT116 and SW48 cell lines are known to harbor epigenetic changes, and were among the most affected by DAC, which may suggest that regulation of DNA methylation in these cell lines is different from that in others. In addition, HCT116 and SW48 cells have been used for the analysis of DNA methylation.…”
Section: Fig 2 Msp Analysis Of the Upstream Region Of Tss In Colon mentioning
confidence: 99%
“…26 LINE-1 methylation has been investigated as a screening tool for cancer detection in blood 27,28 and oral rinse samples 29 as well as a surrogate marker for predicting treatment response to chemotherapy. 30,31 Several studies have demonstrated an association between LINE-1 or ALU hypomethylation and poor clinical outcomes in cancer or clinicopathological parameters indicative of poor prognosis. 12,[32][33][34][35] However, little information is currently available about the prognostic value of repetitive DNA elements in GC.…”
mentioning
confidence: 99%
“…For this reason, other biomarkers and genetic predictors, such as p21, p53, Bax, Bcl2, COX2, VEGF, EGFR and thymidylate synthase [41][42][43], have been studied. Some newly predictive biomarkers are also reported, including Cathepsin S [44], expression of CD133 [45], methylation of long interspersed nuclear element-1(LINE-1) [46], and GRP78 the 78-kDa glucose-regulated protein [47], but some of them are contradictory. These new biomarkers may help predict which patients may respond, but they could not directly translate into widely and low-cost clinical use.…”
Section: Discussionmentioning
confidence: 99%